EVALUASI SISTEM INFORMASI AKADEMIK MENGGUNAKAN FRAMEWORK COBIT 4.1 PADA STIKES AISYIYAH SURAKARTA - Setiyowati Setiyowati; Andriani Kusumaningrum; Muhammad Fitra Ashari (STMIK Sinar Nusantara, 2020)
ABSTRACTThe title of this research report is The Evaluation of Academic Information System (SIAKAD) STIKES Aisyiyah Surakarta using Framework COBIT 4.1. The purpose of this research is to know the level of maturity of the academic Information System (SIAKAD) and formulate recommendations from these results so that it can be useful to assist in the development of academic systems according to standards set by Framework COBIT 4.1 The methods used are data collection (observation, interviews, library study, business document study and questionnaire) and data analysis (calculation of data obtained and analyzed to the final recommendation phase). The result of the evaluation is that the academic information system is well managed. The level of maturity in sub-domains DS1 (Service level management framework), DS5 (System security) and DS10 (Managing problems) is at level 4, which means (managed and measurable), meaning that the agency has been concerned and aware of the importance of Service, system security and management of problems, already has only a few procedures that are still less optimal in its application such as the service of academic information system that has not been connected to the bank payment system.Keywords: Information System, Deliver and Support, COBIT 4.1, Maturity Level